Role of CEO Leadership towards the Performance of Indonesian SOEs - Rudi Rusli; Yuswar Zainul Basri; Willy Arafah (International Review of Management and Marketing, 2020)
The results of this study give us a big picture that the role of the leader in an organization is very important, including companies as large as the SOEs holding company. Companies that have good governance will have an impact on company performance directly and indirectly. Previous research has discussed a lot about leadership and corporate governance in certain companies, especially private companies, but very few studies of corporate governance and leadership have made the SOE holding company its object due to limited access and data. This research informs us that the transformation of CEO leadership and leadership style strategies has a direct and indirect influence on company performance following previous research conducted by several researchers such as Abdelrahman Zuraik, Louise Kelly (2018) and Ozer & Tinaztepe (2014 ). The results of the analysis of this study also found that innovative leadership did not have a significant effect on the performance of SOE holding companies. This was interesting because in several innovative leadership studies it had a significant influence on company performance, observing the condition of SOE holding companies that were governed by quite strict government regulations. thus making the leaders in the SOE holding company restricted to innovating too far from the rules set by the government in terms of policy, but when mediated by organizational identification and the involvement of innovative leadership work has a significant influence in accordance with previous information that the organization in the SOEs holding company has a stronger factor compared to leadership, this is also in accordance with previous research conducted by Wang et al. (2017) Buil et al. (2019) and Soarez & Masquera (2019) who got the same results both in the form of the influence of organizational identification and direct work involvement on company performance. Keywords: Leadership, performance, CEO JEL Classifications: M10, M48, R28 DOI: https://doi.org/10.32479/irmm.9215